Current complications and challenges in nonalcoholic steatohepatitis screening and diagnosis. (2nd January 2016) - Golabi, Pegah; Sayiner, Mehmet; Fazel, Yousef; Koenig, Aaron; Henry, Linda; Younossi, Zobair M
Abstract : Nonalcoholic steatohepatitis (NASH) can lead to complications such as liver failure, cirrhosis and hepatocellular carcinoma. The diagnostic gold standard for NASH is liver biopsy; however, other noninvasive methods have been developed. In this article, the authors evaluate current methods in NASH screening and diagnosis. Routine radiologic modalities were found to detect hepatic steatosis accurately, but were unable to establish the diagnosis of NASH or stage of fibrosis. Newly developed elastography based techniques seem promising to estimate liver fibrosis. Other noninvasive tests such as FibroTest, ELF, Hepascore, FIB-4, NFS, FLI and ION (biochemical panels) have AUROCs ranging between 0.80–0.98 for detecting advanced fibrosis but lack specificity for detecting mild fibrosis. Noninvasive tools, especially elastography, identify NASH associated advanced fibrosis potentially reducing liver biopsies. More research is needed to validate the clinical utility of these tests.